Influence of Adiposity-Related Genetic Markers in a Population of Saudi Arabians Where Other Variables Influencing Obesity May Be Reduced. (17th November 2014) - Alharbi, Khalid K.; Richardson, Tom G.; Khan, Imran Ali; Syed, Rabbani; Mohammed, Abdul Khader; Boustred, Christopher R.; Gaunt, Tom R.; Tamimi, Waleed; Al-Daghri, Nasser M.; Day, Ian N. M.
Abstract : Large scale studies in Europeans have clearly identified common polymorphism affecting BMI and obesity. We undertook a genotype study to examine the impact of variants, known to influence obesity, in a sample from the Saudi Arabian population, notable for its profound combination of low mean physical activity indices and high energy intake. Anthropometry measures and genotypes were obtained for 367 Saudis, taken from King Saud University and Biomarker Screening Project in Riyadh (Riyadh Cohort). We observed large effect sizes with obesity for rs10767664 ( BDNF ) (OR = 1.923, P = 0.00072 ) and rs3751812 ( FTO ) (OR = 1.523, P = 0.016 ) in our sample and, using weighted genetic risk scores, we found strong evidence of a cumulative effect using 11 SNPs taken predominantly from loci principally affecting appetite (OR = 2.57, P = 0.00092 ). We used conditional analyses to discern which of our three highly correlated FTO SNPs were responsible for the observed signal, although we were unable to determine with confidence which best marked the causal site. Our analysis indicates that markers located in loci known to influence fat mass through increased appetite affect obesity in Saudi Arabians to an extent possibly greater than in Europeans. Larger scale studies will be necessary to obtain a precise comparison.